Transdermal Nanogel formulation, development, and evaluation using a synergistic effect of anti-inflammatory drug with herbal extract - Anamika Saxena, Jayshri Hiradas Bairagi, Naidu Narapusetty, GunoSindhu Chakraborthy, Sneha Kacheshwar Sonawane, Kaveripakam Sai Sruthi, R.S. Radke, Ashok Kumar BS, Pushpa T.C. (South Eastern European Journal of Public Health, 2025)
The study intended to design, develop, and assess a transdermal nanogel containing a synergistic combination of herbal extracts and anti-inflammatory and analgesic agents for effective pain and inflammation management. The nanogel was synthesised by a modified emulsion-ultrasonication method, with composition optimised via factorial design to attain the requisite physicochemical characteristics. The composition comprised 6-Gingerol resin and Capsaicin resin, with Nimesulide as the active ingredient and carbopol 940 serving as the gelling agent. Characterisation investigations indicated a mean particle size of 208.12 nm, a narrow particle size distribution of 0.231, and a zeta potential of -12.5 mV, thereby affirming the formulation's stability. The nanogel demonstrated superior viscosity, spreadability, and pH compatibility, rendering it appropriate for transdermal application. Stability experiments performed in accordance with ICH criteria validated the formulation's resilience under diverse situations. The results indicate that the formulated nanogel presents a promising, synergistic treatment strategy for alleviating pain and inflammation while improving patient adherence.